Aplikasi Biochat Tempurung Kelapa dan Pupuk Kandang Sapi terhadap Perubahan beberapa Sifat Fisik Ultisol dan Hasil Tanaman Kacang Tanah - Nasution, Hasriati; Mulyati, Sri; Yusfaneti, Yusfaneti (Bulletin of Community Engagement, 2024)
Peanuts are a secondary crop, belonging to the Leguminoceae family, sub-family Papilionoideae, genus Arachis and Hypogea. As a food crop, peanuts are ranked second after soybeans. Peanuts can be planted in Ultisol soil. Diaman Ultisol is a marginal soil with the characteristics of having a low volume weight, low aggregate stability and also very low water holding capacity and an organic matter content of less than 5%. The aim of the research is to determine the optimal dose of biochar and cow manure for peanut plants. The usefulness of the research results will be to make recommendations for several physical properties of the soil so that the soil can be used sustainably. The research was carried out experimentally by giving Biochat coconut shell and cow manure as a treatment using a Randomized Block Design (RAK) with 6 treatments and 4 replications so that there were 24 experimental plots with a plot size of 2 x 3 m. The parameter observed was the C-organic content. Volume Weight, Total Pore Space, percent of soil aggregate and stability of soil aggregate and peanut crop yield. The results data were analyzed for organic C content, soil volume weight, total pore space, aggregate percentage and aggregate stability and peanut yields were tested using a Randomized Block Design and continued with the Duncan Distance Test at the 5% level (Steel and Torrie, 1995). From the research results, it was found that the mixture of 5 coconut shell Biochat + 5 cow manure and 10 tons of coconut shell Biochat + 10 tons of cow manure was significantly different from other treatments and without giving biochat on soil organic C content, soil volume weight, total space. pores, aggregate percentage, aggregate stability and peanut crop yield. Keywords: Biochat Application, Coconut Shell, Cow Manure